Optimization of injection moulding parameters for recycled high density polyethylene - Ramle, Zuraimi (2017)
Most plastics dispose very slowly in landfills, and these will not only occupy valuable space but will also generate toxic emissions and greenhouse gases such as carbon dioxide. It can remain in the environment for a long period of time, thereby causing problems to the environment and to the health of the society. The practical solution is to recycle and reuse the plastics that have already been used. Nearly all the plastic products that can be seen in our daily life, such as mobile phone housings, automobile bumpers, lunch boxes or bottles are produced by injection moulding. However, incorrect parameter settings in injection moulding will cause bad performance on the specimens such as lack of mechanical strength. Therefore, finding the optimized parameters is highly desirable. This research investigated the usability of recycled HDPE as a substitute for pure HDPE by determines their tensile and flexural strength. The parameters evaluated were melting temperature, injection pressure, holding pressure, holding time, cooling time and injection time. Design Expert 7.0.0 software was used for the screening process by Factorial method and melting temperature, injection pressure and holding time were found as significant parameters. These three parameters then were analysed and optimized by RSM analysis and four process models (tensile of p-HDPE, flexural of p-HDPE, tensile of r-HDPE and flexural of r-HDPE) are successfully developed and validated. The ANOVA suggested that melting temperature is the most significant parameter affecting the tensile and flexural strength of both materials and it was followed by injection pressure and holding time. The optimal result of tensile strength of p-HDPE (27.405 MPa), flexural strength of p-HDPE (21.744 MPa), tensile strength of r-HDPE (15.86 MPa) and flexural strength of r-HDPE (14.353) was obtained at the melting temperature of 240 ºC, injection pressure of 95 MPa and holding time of 30 s. This study also found that the comparison of tensile and flexural strength between p-HDPE and r-HDPE is 42.13% and 33.99% respectively. The specimens of r-HDPE were crushed and injected again by injection machine to produce the specimens. The specimens were tested and compared by the performance of r-HDPE where the reduction of tensile and flexural strength is 10.33% and 20.32% respectively. Some applications such toys, laboratory tubing and plastic pipe have been compared to these three materials based on their strength properties. The result shows the tensile and flexural strength of all materials in the range of the applications strength, and it automatically indicates that r-HDPE can be utilised as a substitutes of p-HDPE in some applications.